2004
DOI: 10.1111/j.1460-9568.2004.03522.x
|View full text |Cite
|
Sign up to set email alerts
|

Prolonged cannabinoid treatment results in spatial working memory deficits and impaired long‐term potentiation in the CA1 region of the hippocampus in vivo

Abstract: Adult male Long-Evans rats were administered the potent cannabinoid 1 receptor agonist HU-210 (100 microg/kg, i.p.) for 15 days continuously and their performance on a matching-to-place version of the Morris water maze was subsequently evaluated. Overall, experimental animals performed significantly worse initially on the reference memory component of this task, but their performance improved over 5 days until it was indistinguishable from that of control animals. Animals given HU-210 did not exhibit working m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
34
4
2

Year Published

2005
2005
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 51 publications
(44 citation statements)
references
References 30 publications
2
34
4
2
Order By: Relevance
“…2a). The positive association between the functional inhibition of anandamide uptake (IC 50 ) and the binding characteristics of LY2318912 (K d ), as well as its displacement with anandamide (K i ), further strengthen the argument that this high-affinity binding site is an anandamide transporter.…”
Section: Results and Conclusionmentioning
confidence: 75%
See 2 more Smart Citations
“…2a). The positive association between the functional inhibition of anandamide uptake (IC 50 ) and the binding characteristics of LY2318912 (K d ), as well as its displacement with anandamide (K i ), further strengthen the argument that this high-affinity binding site is an anandamide transporter.…”
Section: Results and Conclusionmentioning
confidence: 75%
“…Cannabinoid receptor agonists, such as ⌬ 9 -THC, have unwanted side effects, including dulling of short-term memory, psychotropic disturbances (50,51), dependence liability (52), suppression of fertility and the immune system (53,54), and hypolocomotion (55). In contrast, a 30 mg͞kg dose of LY2183240 shows no overt behavioral changes and no performance deficits in the rotorod model in rats (Fig.…”
Section: ) Demonstratingmentioning
confidence: 99%
See 1 more Smart Citation
“…In the hippocampus, this appears to represent the primary means through which cannabinoids acutely disrupt neuronal network activity (Hajos et al 2000). Whereas only a few animal studies have examined the effects of long-term cannabinoid exposure on hippocampal function (Lawston et al 2000;Hampson et al 2003;Hill et al 2004), clinical studies have suggested either that the repeated use of marijuana produces persistent cognitive deficits in humans (Pope and Yurgelun-Todd 1996;Bolla et al 2002), or that these deleterious cognitive effects are reversible (Harrison et al 2002;Pope et al 2002).…”
mentioning
confidence: 99%
“…Chronic 15-day treatment with a potent cannabinoid receptor agonist HU-210 (100 mg/kg i.p.) caused impaired learning in Morris water maze with longer intertrial delays and reduced LTP in the CA1 region of HC tested 18 hours after the last dose (Hill et al, 2004). Both Δ 9 -THC and WIN 55,212-2 decrease PFC DA turnover for up to 2 weeks, suggesting that persistent cognitive disturbances after cannabinoid exposure are possible and perhaps Drug-Induced Neuroplasticity at least partly related to the reduction in the DA transmission in the PFC (Verrico et al, 2003).…”
Section: Drug-induced Neuroplasticitymentioning
confidence: 99%